2021
DOI: 10.1002/adfm.202107726
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Tolerant Printing for Scalable and Flexible Perovskite Solar Cells

Abstract: Homogeneity and stability of flexible perovskite solar cells (PSCs) are significant for the commercial feasibility in upscaling fabrication. Concretely, the mismatching between bottom interface and perovskite precursor ink can cause uncontrollable crystallization and undesired dangling bonds during the printing process. Herein, methylammonium acetate, serving as ink assistant (IAS) can effectively avoid the micron-scale defects of perovskite film. The in situ optical microscope is applied to prove the IAS can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 48 publications
0
65
0
Order By: Relevance
“…This trend is consistent with previous studies. [38] Furthermore, the charge density difference of the adsorption structures also intuitively reflects the strong interaction of CBSA/perovskite (Figure 3d). The highly electronegative chlorine atoms inductively withdraw electron density, which reduces the electron density of the less electronegative iodine on the bottom of perovskite, thus achieving the effective passivation of Pb-I defects on the bottom of perovskite.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…This trend is consistent with previous studies. [38] Furthermore, the charge density difference of the adsorption structures also intuitively reflects the strong interaction of CBSA/perovskite (Figure 3d). The highly electronegative chlorine atoms inductively withdraw electron density, which reduces the electron density of the less electronegative iodine on the bottom of perovskite, thus achieving the effective passivation of Pb-I defects on the bottom of perovskite.…”
Section: Resultsmentioning
confidence: 88%
“…The previous studies have confirmed that nonradiative trapping assisted recombination is considered to be the main recombination pathway in the reverse PVSCs. [38] In terms of the dependence of V oc on the illumination intensity, the unit slope β deviation from 1 (1/k B Tq) reflects the recombination probability (where β is slope of V oc versus log-scaled light intensity, k is the Boltzmann constant, and q is the elementary charge). As show in Figure 4e, the exponent β of device based on NiO x /CBSA is closer to 1, implying that trap-assisted recombination in NiO x / perovskite interface has been effectively suppressed.…”
Section: Resultsmentioning
confidence: 99%
“…The shift of the Cl signal peaks may be due to the electronegativity of the covalent Cl − is lower than that of I − , and its electron withdrawing ability is weaker. As shown in Figure S6a, for KAcCl 2 doping, this shift phenomenon is more obvious than KAc, indicating that there is a stronger coordination with Pb 2+ in KAcCl 2 doping due to the simultaneous presence of oxygen and chlorine atoms, which can better passivate lead iodide defects [42,43] . In addition, the obvious Pb 0 signal appears in the XPS spectrum of the control group perovskite.…”
Section: Resultsmentioning
confidence: 93%
“…As shown in Figure S6a, for KAcCl 2 doping, this shift phenomenon is more obvious than KAc, indicating that there is a stronger coordination with Pb 2 + in KAcCl 2 doping due to the simultaneous presence of oxygen and chlorine atoms, which can better passivate lead iodide defects. [42,43] In addition, the obvious Pb 0 signal appears in the XPS spectrum of the control group perovskite. The metallic lead is produced by the decomposition of the perovskite film in the air environment, which will deteriorate the performance of the device.…”
Section: Resultsmentioning
confidence: 97%
“…[2] Meanwhile, flexible devices have also reached the highest PCE of 21.05%. [3] The merits of PSCs, such as low cost, suitable bandgaps for indoor light sources such as lightemitting diodes (LEDs), and simply fabricating flexible devices, [4][5][6][7] also enhance the indoor commercialization possibility. [8] In the past several years, research on indoor photovoltaics has also accelerated, which promotes the realization of the idea of the indoor Internet of Things (IoT) in the future.…”
mentioning
confidence: 99%